Implosion tests of aluminium-alloy ring-stiffened cylinders subjected to external hydrostatic pressure. (July 2021) - Muttaqie, Teguh; Park, Sang Hyun; Sohn, Jung Min; Cho, Sang-Rai; Nho, In Sik; Han, Soonhung; Cho, Yoon Sik
Abstract: In this paper, the dynamic implosion responses of ring-stiffened cylindrical tubes under external hydrostatic pressure are reported. The ring-stiffened cylinder models were fabricated from commercial seamless aluminium-alloy 6061-T6 tubes. Six external stiffened models were constructed: three models with three stiffeners, and the other three with five stiffeners. To quantify the effects of stiffening on the structural behaviour, implosion tests were also performed on another three unstiffened tube models. In this study, a total of nine tube models were tested until their failure. Implosion was initiated by increasing the hydrostatic pressure in the chamber until the tubes collapsed, and the effects of different types of pressurising media were investigated: (i) water only and (ii) water and nitrogen gas combined. The implosion pressure pulse near the collapsing tube was recorded during the event. The models with five stiffeners increased the implosion pressure pulse by approximately 3.5 times compared with the unstiffened model. Highlights: Experimental investigation of implosion response of ring-stiffened aluminium-alloy tube. The effects of stiffening on the implosion response was studied. The dynamic pressure generated during the implosion was measured and compared. The effects of different pressurising media were investigated: (i) water only; (ii) combined water and nitrogen.